Modern Interpretation of Essence of Profit As a Source For Forming Financial Resources - Alieva , S.S (Indonesian Journal of Innovation Studies, 2019)
The article is devoted to the characterization of the nature of profit, the sources of its occurrence, factors affecting the mechanism of profit generation, competition, which arises for the purpose of making a profit depending on the type of market structure. The nature of profit is considered from the point of view of a critical analysis of the theories of various economic schools, assessments of their weak and strong points.